Effect of Thunbergia laurifolia Herbal Tea on Glucose Homeostasis in Healthy Volunteers: A Single-Arm Phase I Study. (23rd July 2020) - Preechasuk, Lukana; Akarasereenont, Pravit; Boonrak, Ranida; Thamsermsang, Onusa; Pratumvinit, Busadee; Thongtang, Nuntakorn
Abstract : Background . Thunbergia laurifolia (TL) is a commonly used herbal medicine in Thailand and in other Asian countries. TL has been approved as a Thai traditional medicine for detoxifying poisons, and the list of possible adverse effects includes hypoglycemia. TL showed hypoglycemic effect in animals possibly due to antioxidant effect and beta-cell preservation. However, the safety of TL herbal tea and its effects on glucose homeostasis have never been investigated in humans. Methods . Twenty healthy volunteers (10 men and 10 women) drank TL herbal tea 3 times/day for 2 weeks. Ten subjects took TL herbal tea 9 grams daily. After the safety of TL herbal tea was established, 10 more subjects took TL 12 grams daily. Clinical and biochemical tests were assessed at baseline and at 2 weeks. Results . Mean age was 34.9 ± 10.2 years, and mean body mass index was 27.5 ± 5.8 kg/m 2 . Baseline and posttreatment plasma concentrations were as follows: fasting plasma glucose (89 ± 6 vs . 89 ± 7 mg/dL), fructosamine (213 ± 32 vs . 212 ± 33  μ mol/L), fasting insulin (8.8 [IQR: 5.9–18.4] vs . 10.4 [IQR: 7.4–15.2] μ U/mL), HOMA-B (101.6 [IQR: 82.3–189.8] vs . 120.4 [IQR: 93.2–153.2]), and HOMA-IR (1.1 [IQR: 0.8–2.3] vs . 1.4 [IQR: 0.9–2.0]), all respectively. There were no significant changes in these parameters, including body weight, blood pressure, lipid profile, and C-reactive protein. No serious adverse events were observed during the study period. Conclusions . TL herbal tea at doses of 9 and 12 grams daily had good tolerability without any significant adverse effects on fasting plasma glucose level or other glucose homeostasis parameters measured.